Comparison of intercanine width in between Angle class II division 1 and division 2 malocclusions - Putri, Bebby; Malik, Isnaniyah; Zenab, N R Yuliawati (Padjadjaran Journal of Dentistry, 2016)
Introduction: Dental arch width measurement is needed to determine diagnoses and orthodontic treatment planning of Angle Class II Division 1 and Class II Division 2  malocclusions that have narrow maxillary dental arch generally. Dental arch width in this study was measured by maxillary and mandibular intercanine width.  This study aimed to compare the differences of intercanine width between Angle Class II division 1 and Class II division 2 malocclusions. Methods: Descriptive comparative research with total samples of 67 study models, consisted of 34 Class II division 1 cases and 33 Class II division 2 cases. The minimum age of the samples chosen was 13 years old with no history of orthodontic treatment. A non probability consecutive sampling technique was used. Results: Study results showed the avarage maxillary and mandibular intercanine width of Class II Division 1 were 33,99 mm and 26,33 mm. Average maxillary and mandibular intercanine width of Class II Division 2 were 34,77 mm and 25,37 mm. Conclusions: T-test analysis showed no statistical significant differences in the intercanine width between Angle Class II Division 1 and Class II Division 2  malocclusions.